Pengaruh Pendapatan dan Biaya Operasional terhadap Laba Bersih Perusahaan IDX Basic Materials dan IDX Industrials - Muhammad Fiqrianto; Cynthia Eka Violita; Achmad Zaki; M. Mustaqim (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of revenue and operating costs on net profit in companies in the IDX Basic Materials and IDX Industrials sectors listed on the Indonesia Stock Exchange for the 2022–2024 period. This study uses a quantitative approach with secondary data obtained from the companies' annual financial reports. The research sample was determined using a purposive sampling technique, resulting in 68 companies with a total of 204 observations. Data analysis was performed using multiple linear regression with the help of the IBM SPSS 27 program and through classical assumption testing, t-test, F-test, and coefficient of determination. The results show that revenue has a positive and significant effect on net profit. Operating costs also have a positive and significant effect on net profit. Simultaneously, revenue and operating costs have a significant effect on net profit. The Adjusted R Square value of 0.805 indicates that 80.5% of the variation in net profit can be explained by these two independent variables, while the remainder is influenced by other factors outside the study. This study makes an empirical contribution to the development of accounting and financial management literature by providing current evidence regarding the effect of revenue and operating costs on net profit in companies in the IDX Basic Materials and IDX Industrials sectors. In addition, the results of this study can be used as a consideration for company management and investors in evaluating financial performance and formulating strategies to increase company profitability.